Flood Risk Management as a public or a private good, and the implications for stakeholder engagement - Geaves, LH; Penning-Rowsell, EC (Elsevier, 2015)
A move to encourage partnership funding of Flood Risk Management (FRM) has resulted in current FRM measures providing both public and private benefits. Yet, the scales of service delivery associated with public and private goods are likely to influence the form and extent of public participation in FRM. We assess the range of goods provided by FRM, whether these services are considered to be public in nature by authorities and citizens, and the impact this has upon the level and form of public engagement in FRM. We separate the definitions of public goods into ‘pure’ public goods which demonstrate characteristics of non-rivalry and non-excludability, and public priority goods which are services deemed as essential to public wellbeing regardless of characteristics. We find that English FRM delivers a range of public goods beyond that of reduced water flows, and that when FRM is considered a ‘pure’ public good the emergent form of public participation does not increase public awareness of flood risk or encourage investment in private protection measures. When the benefits of FRM are solely considered public priority goods public awareness of flood risk increases, yet disputes arise regarding service provision and maintenance. Importantly, increased flood risk from climate change or increased runoff could lead to the capacity of the public good provision being exceeded, leading to problems of distribution of that service, and reactionary pressure group formation. We argue that the current preference for public goods which reduce individual costs at the expense of public awareness can discourage adaptation, which may be problematic in ensuring sustainable FRM.